Transnational corporations and the manufacturing sector in Brasil. technological backwardness in the eighties and signs of an important restructuring in the nineties. CEPAL (CEPAL, 1993)
Este folleto es un resumen de los principales descubrimientos de un estudio sobre TNCS y cambios estructurales en el sector manufacturero brasileño